New Trouble For Deliberative Democracy - Talisse, Robert (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2017)
In the past two decades, democratic political practice has taken a deliberative turn. That is, contemporary democratic politics has become increasingly focused on facilitating citizen participation in the public exchange of reasons. Although the deliberative turn in democratic practice is in several respects welcome, the technological and communicative advances that have facilitated it also make possible new kinds of deliberative democratic pathology. This essay calls attention to and examines new epistemological troubles for public deliberation enacted under contemporary conditions. Drawing from a lesson offered by Lyn Sanders two decades ago, the paper raises the concern that the deliberative turn in democratic practice has counter-democratic effects.